2007
DOI: 10.3177/jnsv.53.515
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Fatty Acids in Milk as the Regulator of the Expression of Cytosolic Binding Proteins for Fatty Acids and Vitamin A through PPAR.ALPHA. in Developing Rats

Abstract: Summary Fatty acids in milk are thought to play an important role in intestinal maturation and gene expression in the postnatal small intestine. In this study, we determined the jejunal mRNA levels, in rats, of peroxisome proliferator-activated receptor ␣ (PPAR ␣ ) and PPAR ␦ which are nuclear receptors for fatty acids. We also measured expression of their target genes during the postnatal period, namely liver type fatty acid-binding protein (L-FABP) and cellular retinol-binding protein, type II (CRBPII). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…The two major isoforms of FABP found in enterocytes, intestinal-type (I-FABP) and liver-type (L-FABP), are known to have different binding specificity and their mRNA levels have previously been studied in rats during postnatal intestinal development. I-FABP mRNA levels remain constant during the suckling period, whereas the mRNA levels of L-FABP gradually increase during the suckling period and then sharply declines at the end of weaning (17,20). We identified both isoforms, which showed different expression profiles in comparison to the mentioned previous studies (Table I).…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-contrasting
confidence: 46%
“…The two major isoforms of FABP found in enterocytes, intestinal-type (I-FABP) and liver-type (L-FABP), are known to have different binding specificity and their mRNA levels have previously been studied in rats during postnatal intestinal development. I-FABP mRNA levels remain constant during the suckling period, whereas the mRNA levels of L-FABP gradually increase during the suckling period and then sharply declines at the end of weaning (17,20). We identified both isoforms, which showed different expression profiles in comparison to the mentioned previous studies (Table I).…”
Section: Establishment Of Label-free Quantitative Proteomics Of In-contrasting
confidence: 46%
“…Slc27a2 plays a key role in ␤-oxidation (44). Higher expression of Slc27a2 during the suckling period in the jejunum may be important for energy generation from fat because milk contains large amounts of fat and our previous studies showed that the gene expressions of rate-controlling enzymes of ␤-oxidation, such as acyl-CoA oxidase, are highly expressed during the suckling-weaning period (6,7). We also detected the zinc transporter Slc30a2 (45) among the downregulated genes.…”
Section: Discussionmentioning
confidence: 63%
“…It is necessary in further studies to examine whether these transcriptional factors regulate the genes downregulated during the sucklingweaning period. Our recent studies indicated that the expressions of genes related to dietary fat absorption and ␤-oxidation in the rat small intestine during suckling are enhanced by dietary fat in milk through activation of the nuclear receptor PPAR␣, which directly binds fatty acids as ligands (6,7). Another recent study revealed that Slc27a2 in the mouse small intestine is induced by PPAR␣ (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also demonstrated that jejunal expression of genes related to nutrient absorption such as cellular retinol-binding protein, type II (CRBPII) and liver-type fatty-acid binding protein (L-FABP) are regulated by another subtype of PPAR, i.e., PPAR␣ (35). During the postnatal period, the PPAR␣ gene is highly expressed during the suckling-weaning transient period from 13 to 20 d after birth (36). Thus, PPAR␣ may be also concerned with the induction of the jejunal BCMO1 gene confi ned to the period between days 13 and 20 after birth.…”
Section: Discussionmentioning
confidence: 99%